SISTEM INFORMASI INVENTORI PERPUSTAKAAN DI UPN “VETERAN” YOGYAKARTA - Paryati Paryati (Jurusan Teknik Informatika, 2016)
Inventory library information system aims to increase the information service effectively and efficiently. It also intends to increase the activity of the library by changing the old system with new system at present through computerization system, because by using the computerization system the modules can be devide into simpler so that it is easy to understand. The new system, uses computer as a tool to process the electronic data. The circulation data deals with the acceptance and the stock of books is processed by the computer then stored as file. With the modern information technology processing, data can be process in accordance with the need and high capacity to keep the data in the large amount. The cost needed is more efficient because the separated files are taken into one with the data base so that it pushes the book circulation process functions integration and only involve some energy as the operator therefore the information can be got quickly, accurately with the high accuracy because by using the computer it is good in doing the repeatedly work so that in taking the decision can be done soon to increase the service of the user.